Guide of strategies for urban regeneration: A design-support tool for the Spanish context. (May 2016) - Mateo, C.; Cuñat, A.
Highlights: What is missing? Identifying thematic gaps in existing urban assessment tools. Does reality match rhetoric? Urban assessment tools applicability to selected best practices. Which are the socio-technical barriers? Interviews to regional decision-makers. How to proceed? Proposal of a design-support tool for the Spanish context. Abstract: Recent studies reveal physical, economical, and socio-technical barriers when measuring performance of sustainable urban ration projects with existing assessment tools. This reality, enlarged in the Spanish context, has revealed the need of a friendly-user and holistic tool that can assist the agents involved in the decision-making process of urban regeneration projects. This paper presents the Guide of strategies for urban regeneration; a design-support tool developed by demand of the Government of the Valencian Community (Spain). Along this paper we describe how the Guide has been designed by integrating: in first place measures of exiting urban assessment tools, secondly lesson learned coming from the application of urban assessment tools to selected and rewarded urban best practices at European level, and thirdly the opinion of regional decision-makers and urban experts. As a result, this Guide offers strategies and recommendations on a self-questioning format that makes easy its implementation by any urban planner regardless of its expertise on the topic. It is based on an open-source philosophy with a nonprofit orientation, using transparent and easy-to-understand technical criteria. It can be applied to any kind of urban fabric and proposes equal representation of the thematic categories needed to be considered during an urban regeneration project design.